Dose-independent pharmacokinetics of loganin in rats: effect of intestinal first-pass metabolism on bioavailability - Park, Hwi Jin; Bae, Sung Hun; Kim, So Hee (Journal of Pharmaceutical Investigation, 2021)
Purpose: Loganin, one of the two main iridoid glycosides in Cornus officinalis Sieb et Zucc, has been reported to exhibit many biological activities such as immune modulation, as well as anti-inflammatory and anti-shock effects. This study was designed to evaluate the pharmacokinetics of loganin, administered intravenously (5, 10, 20 and 50 mg/kg) and orally (20, 50, 100 and 200 mg/kg), in rats. Methods: To evaluate its hepatic and gastrointestinal first-pass effects, loganin was administered intraportally, intragastrically and intraduodenally to rats. Results: Following intravenous administration of 5–50 mg/kg loganin, a linear relationship was observed between the total area under the plasma concentration–time curve from zero to infinity (AUC) and loganin dose, with ~ 19% of the administered dose excreted in the urine. AUCs following oral administration of 20–200 mg/kg loganin were dose-independent, with the extent of absolute oral bioavailability (F) being approximately 4.87%. The AUC of loganin was significantly lower by 90.6% after intraduodenal than intraportal administration, but did not differ between intragastric and intraduodenal administration. The AUC was also significantly lower by 52.7% after intraportal, compared to intravenous, administration, suggesting that the hepatic first-pass effect on loganin after entering the portal vein was approximately 4.95% of the oral dose. Conclusion: Taken together, our data suggest that the low F of loganin in rats was due exclusively to its high intestinal first-pass metabolism.
Keywords: Dose-independent; Intestinal first-pass metabolism; Loganin; Pharmacokinetics; Rats